Glycemic profile variability as an independent predictor of diabetic retinopathy in patients with type 2 diabetes: a prospective cohort study - Dehghani Firouzabadi, Fatemeh; Poopak, Amirhossein; Samimi, Sahar; Deravi, Niloofar; Nakhaei, Pooria; Sheikhy, Ali; Moosaie, Fatemeh; Rabizadeh, Soghra; Meysamie, Alipasha; Nakhjavani, Manouchehr; Esteghamati, Alireza (Frontiers in Endocrinology, 2024)
Background Glycemic variability is a novel predictor for diabetic complications. Different studies have demonstrated contradictory results for the association between HbA1c variability and diabetic retinopathy. We aimed to assess the relationship between visit-to-visit variability in glycemic profile (HbA1c, 2hPP, and FBS) and diabetic retinopathy. Methods Patients with type 2 diabetes were monitored for the development of retinopathy for 10 years. The association between the incidence of retinopathy and glycemic variability was assessed via Cox regression analysis, and coefficient of variation for glycemic indices was compared using independent sample t-test. Results Patients with diabetic retinopathy had significantly higher glycemic profile variability. The incidence of retinopathy was positively correlated with cv-FBS10% (10% of coefficient of variance), cv-FBS20%, cv-2hpp10%, and cv-HbA1c5%. Our analysis revealed that the higher variability of FBS increased the incidence and progression of retinopathy (HR: 12.29, p-value = 0.003). Conclusion Our findings demonstrated glycemic profile variability as an independent risk factor for diabetic retinopathy in patients with type 2 diabetes and support glycemic profile variability measurement in addition to common glycemic parameters to improve risk stratification in patients with type 2 diabetes. Further investigation is required to demonstrate the long-term effects of alleviating glycemic variability on the prognosis of patients with type 2 diabetes.